2024
DOI: 10.3390/app14020938
|View full text |Cite
|
Sign up to set email alerts
|

PRC-Light YOLO: An Efficient Lightweight Model for Fabric Defect Detection

Baobao Liu,
Heying Wang,
Zifan Cao
et al.

Abstract: Defect detection holds significant importance in improving the overall quality of fabric manufacturing. To improve the effectiveness and accuracy of fabric defect detection, we propose the PRC-Light YOLO model for fabric defect detection and establish a detection system. Firstly, we have improved YOLOv7 by integrating new convolution operators into the Extended-Efficient Layer Aggregation Network for optimized feature extraction, reducing computations while capturing spatial features effectively. Secondly, to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…YOLO v8 achieves the highest precision, the mAP and F1-scores were 75.3% and 0.732, respectively, while the YOLO v5 model has the second highest accuracy, indicating that the YOLO series models have strong detection capabilities compared to the other modules. Although there is limited research on YOLO v8, the relevant studies also confirmed the superiority of the recently released YOLO series in object detection [58][59][60][61].…”
Section: Individual Tree Species Identification Results Of Different ...mentioning
confidence: 79%
“…YOLO v8 achieves the highest precision, the mAP and F1-scores were 75.3% and 0.732, respectively, while the YOLO v5 model has the second highest accuracy, indicating that the YOLO series models have strong detection capabilities compared to the other modules. Although there is limited research on YOLO v8, the relevant studies also confirmed the superiority of the recently released YOLO series in object detection [58][59][60][61].…”
Section: Individual Tree Species Identification Results Of Different ...mentioning
confidence: 79%
“…This technique extracts cross-modal discriminant information, thereby improving the accuracy of detecting small targets. Moreover, Liu et al [ 31 ] enhanced YOLOv7, integrated a new convolution operator into the backbone network, and extended the sensitivity field; thus, they reduced the parameters by 18.03% and computed the load of the defect detection model that was equal to 20.53%. In addition, Zhu et al [ 32 ] proposed a variety of SSD-based modules to detect concrete cracks, where the feature fusion-enhanced module can effectively fuse the feature channel information to enhance object detection precision.…”
Section: Introductionmentioning
confidence: 99%